Students’ Satisfaction on Housing Services: Basis of Management Plan in the New Normal - Orlando A. Batara; Cherie Orpia (Journal of Education Review Provision, 2022)
The study was conducted to benefit the student boarders, dormitory/boarding house owners, and proprietors to create awareness of the needs and problems of the student boarders of Ilocos Sur Polytechnic State College, Santa Maria, Ilocos Sur, Philippines. Thus, the study aimed to create a plan to improve the management and services of the students. The study employed a descriptive-correlational and developmental research design where the profile, satisfaction level on various services were gathered, and a dormitory/boarding house management plan was formulated. The result shows that most of the respondents were single, bed spacers, and staying in dormitories or boarding houses outside the campus. Moreover, there was a significant relationship among the dimensions, which signified that the factors were essential to increasing the students' level of satisfaction. In addition, significant differences among the boarders staying within the campus and outside the campus were noted on the factors such as religious services, dorm/boarding house policy, and student safety and conduciveness for learning. A proposed boarding house/dormitory management plan is proposed focusing on physical facilities, utilities, financial services, religious services, and student safety and conduciveness for learning. This is to ensure access to accommodation that is safe and conducive to the students' learning.